Deixis and Digital Persuasion: Sociopreneurship Messages of @aldwinnv on Instagram and TikTok - Ari Astutik; Dewanto; Lambang Erwanto (Proceeding International Conference on Education, 2025)
This study looks at how deixis shapes persuasive sociopreneurship posts on Instagram and TikTok, using six posts by Indonesian sociopreneur @aldwinnv as examples. Deixis, which links language to the speaker, audience, and context, plays a key role in how messages persuade online. By analyzing the posts with a qualitative descriptive approach, the study highlights five types of deixis: personal, temporal, spatial, social, and discourse. Words like I and we (personal deixis) build trust and closeness with followers. Temporal cues such as now and today create a sense of urgency, pushing readers to take action. Spatial references, like here or this place, make the stories feel grounded and real. Social deixis—terms like friends or guys—varies in tone: more formal on Instagram, more casual and friendly on TikTok. Discourse markers such as as I mentioned earlier help the narrative flow and stay coherent. In short, deixis isn’t just a technical language feature-it’s a persuasive tool. It strengthens credibility, engages emotions, and fosters a sense of community around sociopreneurship content. This research adds to digital pragmatics by showing how small language choices can have a big impact and offers practical insights for teaching media literacy and entrepreneurship.